KUALITAS PELAYANAN PEMBUATAN SERTIFIKAT TANAH DI KABUPATEN MINAHASA SELATAN - RUMENGAN, FERON; TULUSAN, FEMMY; LONDA, VERY (Sam Ratulangi University, 2019)
Bureaucratic behavior is essentially the result of bureaucratic interaction as a collection of individualswith their environment. Deviant bureaucratic behavior is more accurately seen as a bureaucraticpathology or a symptom of bureaucratic deviation. In relation to bureaucratic behavior in providingservices in the sub-district, its position, role, and function cannot be separated from individuals as subdistrictofficials (employees) who have perceptions, values, motivation, and knowledge in order to carryout social duties, functions, and responsibilities in providing services. Human behavior in organizationslargely determines the achievement of maximum results in order to achieve organizational goals.Human behavior is a function of the interaction between individuals and their environment. Eachindividual has its own characteristics, and these characteristics will be brought when he entered acertain environment. These characteristics include abilities, personal beliefs, needs, and experience.Likewise, organizations within the sub-district scope of each individual (bureaucrat) have certaincharacteristics, namely the order that is realized in the hierarchy, work, tasks, authority andresponsibility, so that they are required to be able and consistent in providing services to thecommunity.Keywords: Behavior, Bureaucracy, Public Service